(untitled) (European Journal of Emerging Technology and Discoveries, 2025)
The current study aims to demonstrate the impact of applying the sustainable quality management system in enhancing Operations performance, as an administrative approach that provides the possibility of improving best practices and expanding them in the future, based on the fact that quality creates value for customers and society by supporting the sustainability triad (economic, social, environmental) through continuous improvement in Operations performance and innovation. The issue of the investigation is described in the volume of the effect of applying a sustainable quality management system to improve Operations effectiveness. The significance of the study is in providing light on the sustainable method of quality management that can be used to help organizations improve their Operations performance and have significant results while also maintaining a sustainable nature that contributes to the prosperity of societies and increases the competitiveness of organizations. To accomplish the goals of the study, a questionnaire with 40 items was employed. The purpose of the investigation was to formulate two basic hypotheses. To assess the legitimacy and fidelity of the results, a variety of statistical methods were employed using statistical programs (SPSS.ver.24) and (AMOS.ver.24). The findings of the study showed a significant association and influence between the sustainable quality management system and Operations performance.